Underfill adhesive as well as preparation method and application thereof
By synergistically using fillers, silver nanowires and sheet boron nitride in the underfill glue, the problem of difficult to balance thermal conductivity, fluidity and mechanical properties in the prior art is solved, and the high thermal conductivity, fluidity and mechanical properties are achieved, and the thermal performance and connection reliability of chip packaging are improved.
Patent Information
- Application Number
- CN202411994543.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
Existing underfill glues are difficult to maintain high flowability and good mechanical properties while improving thermal conductivity, resulting in thermal stress and connection reliability problems in chip packaging.
By synergistically acting in the underfill glue, silver nanowires and sheet boron nitride, the amount used is controlled within a specific range, and an underfill glue with high thermal conductivity and high fluidity and good mechanical properties are prepared.
The high thermal conductivity, fluidity and mechanical properties of the underfill glue are achieved, which improves the thermal performance and connection reliability of the chip package and reduces the possibility of thermal stress.
Smart Images

Figure CN119775937A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of packaging materials, and in particular relates to a bottom filling glue and a preparation method and application thereof. Background Art
[0002] As electronic devices continue to develop towards miniaturization and high functionality, the demand for high-density packaged semiconductor chips and other electronic components is growing. Flip chip technology is widely used due to its smaller package size, narrower pitch and high I / O density. However, due to the difference in thermal expansion coefficients between the silicon chip and the substrate, stress may be generated at the connection. If not properly relieved, it may cause cracks at the connection, thus affecting the reliability of the connection. In order to improve the mechanical connection strength and reduce the solder joint stress caused by the mismatch of thermal expansion coefficients, bottom filler is usually used between the chip and the substrate. This filler is mainly composed of a large amount of cured epoxy resin filled with silica filler. The cured epoxy resin has excellent electrical insulation, high modulus and strength, and good adhesion at different interfaces, so it is an ideal bottom filler matrix material. However, the miniaturization of the package also puts higher requirements on the thermal conductivity of the material.
[0003] The bottom filler needs to have good thermal conductivity so that the heat generated by the chip can be quickly transferred to the cooling system. This can effectively reduce the chip temperature and prevent overheating, thereby ensuring the performance and life of the electronic device. Good thermal conductivity helps to form a uniform temperature distribution between the chip and the substrate, reduce the thermal stress caused by local high temperature, and improve the stability of the package. The thermal conductivity of the bottom filler directly affects the overall reliability of the package. High thermal conductivity materials can more effectively alleviate the stress caused by the mismatch of thermal expansion coefficients and reduce the possibility of cracks and failures. Therefore, it is very necessary to develop a high thermal conductivity bottom filler.
[0004] Improving the thermal conductivity of the bottom filler is one of the key measures to improve the thermal performance of electronic packaging. Using bottom filler materials with better thermal conductivity is the most direct way to reduce thermal conductivity. However, traditional thermal conductive fillers such as boron nitride and diamond powder require a higher filling amount to achieve ideal thermal and mechanical properties, but a higher filling amount will reduce the fluidity of the material, which brings difficulties to practical applications.
[0005] Therefore, how to provide a bottom filling glue that has both high thermal conductivity and high fluidity as well as good mechanical properties has become a technical problem that needs to be solved urgently. Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention aims to provide an underfill and a preparation method and application thereof. The present invention designs the specific composition of the underfill, and further prepares an underfill having both high thermal conductivity and high fluidity as well as good mechanical properties through the synergistic effect of fillers, silver nanowires and flake boron nitride.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides an underfill adhesive, wherein the underfill adhesive comprises the following components in parts by weight:
[0009]
[0010] The present invention designs the specific composition of the bottom filling glue, and further prepares the bottom filling glue with high thermal conductivity and high fluidity as well as good mechanical properties through the synergistic effect of fillers, silver nanowires and flaky boron nitride.
[0011] In the present invention, silver nanowires and flaky boron nitride as efficient thermal conductive fillers can significantly improve the thermal conductivity of the bottom filling material at a relatively low filling amount and maintain its good flow filling property; and the filler (spherical nano-silicon dioxide) in the formula can also maintain the mechanical properties of the bottom filling material while ensuring good fluidity.
[0012] In the present invention, by controlling the amount of silver nanowires to be within a specific range, an underfill with excellent comprehensive performance is prepared. If the amount of silver nanowires is too little, it is difficult to form a thermal conductive network; if the amount of silver nanowires is too much, the cost is greatly increased and the fluidity of the system is reduced.
[0013] At the same time, the present invention controls the amount of flaky boron nitride to be within a specific range, thereby preparing an underfill with excellent comprehensive performance. If the amount of flaky boron nitride is too little, it is difficult to form a thermal conductive layer; if the amount of flaky boron nitride is too much, the fluidity of the system is reduced.
[0014] In the present invention, the weight proportion of the epoxy resin in the bottom filling glue can be 35 parts, 36 parts, 37 parts, 38 parts, 39 parts, 40 parts, 41 parts, 42 parts, 43 parts, 44 parts or 45 parts.
[0015] The weight proportion of the curing agent in the bottom filling adhesive may be 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts or 20 parts, etc.
[0016] The weight proportion of the filler in the bottom filling glue can be 32 parts, 33 parts, 34 parts, 35 parts, 36 parts, 37 parts, 38 parts, 39 parts or 40 parts, etc.
[0017] The weight proportion of the silver nanowires in the bottom filling glue can be 0.4 parts, 0.42 parts, 0.46 parts, 0.48 parts, 0.5 parts, 0.52 parts, 0.54 parts, 0.56 parts, 0.58 parts or 0.6 parts, etc.
[0018] The weight proportions of epoxy resin in the bottom filling glue can be 5 parts, 5.2 parts, 5.5 parts, 5.7 parts, 6 parts, 6.3 parts, 6.6 parts, 6.8 parts, 7 parts, 7.2 parts, 7.5 parts, 7.8 parts or 8 parts, etc.
[0019] In the present invention, BN represents flake boron nitride, and AgNM represents silver nanowire, and the same shall apply hereinafter.
[0020] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.
[0021] As a preferred technical solution of the present invention, the aspect ratio of the silver nanowires is ≥150, for example, it can be 150, 155, 160, 165, 170, 175, 180, 185, 190, 195 or 200, etc.
[0022] In the present invention, by selecting silver nanowires with a high aspect ratio within a specific range, a bottom filling adhesive with excellent comprehensive performance is prepared. If the aspect ratio of the silver nanowires is too low, it is not conducive to forming a thermal conductive network.
[0023] The present invention further optimizes the comprehensive performance of the bottom filling glue by further optimizing the aspect ratio of the silver nanowire within a specific range.
[0024] Preferably, the silver nanowire has a length of 10-20 μm (for example, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm or 20 μm, etc.), and a diameter of 20-60 nm (for example, 20 nm, 24 nm, 28 nm, 30 nm, 32 nm, 36 nm, 40 nm, 44 nm, 46 nm, 50 nm, 52 nm, 56 nm or 60 nm, etc.).
[0025] Preferably, the silver nanowires are well dispersed in ethanol. Good dispersibility is a prerequisite for uniform mixing. The silver nanowires can remain in a suspension state in ethanol for more than one week.
[0026] As a preferred technical solution of the present invention, the average particle size of the flaky boron nitride is 3-5 μm, for example, it can be 3 μm, 3.2 μm, 3.4 μm, 3.6 μm, 3.8 μm, 4 μm, 4.2 μm, 4.4 μm, 4.6 μm, 4.8 μm or 5 μm.
[0027] The present invention prepares an underfill with excellent comprehensive performance by designing the average particle size of the flake boron nitride within a specific range. If the average particle size of the flake boron nitride is too small, it is not conducive to maintaining the fluidity of the system; if the average particle size of the flake boron nitride is too large, it is not conducive to the mechanical properties of the underfill.
[0028] Preferably, the thickness of the flake boron nitride is less than 100 nm, for example, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm or 100 nm.
[0029] Preferably, the flaky boron nitride comprises modified flaky boron nitride, and the modifier of the modified flaky boron nitride comprises any one or a combination of at least two of cationic polyacrylamide (CPAM), anionic polyacrylamide (APAM), zwitterionic polyacrylamide (Am-PAM) and non-ionic polyacrylamide (NPAM), and is further preferably cationic polyacrylamide (CPAM).
[0030] Preferably, the mass ratio of the modifier to the flake boron nitride is 1:(100-200), for example, it can be 1:100, 1:110, 1:120, 1:130, 1:140, 1:150, 1:160, 1:170, 1:180, 1:190 or 1:200, etc.
[0031] It should be noted that the present invention has no special restrictions on the preparation method of modified flaky boron nitride, and the commonly used modification methods in the art are applicable. Taking the modifier as cationic polyacrylamide as an example, the preparation method of modified flaky boron nitride includes the following steps:
[0032] BN powder and deionized water were placed in a flask equipped with a mechanical stirrer, and then ultrasonically treated for 10 min at a power of 200 W, and then mechanically stirred at 500 rpm for 5 min to obtain a BN suspension;
[0033] Then, a 1 wt% cationic polyacrylamide aqueous solution (cationic polyacrylamide was purchased from Aladdin, item number P754420) was added dropwise to the BN suspension until the suspension became transparent to obtain a mixture, and the obtained mixture was filtered and washed three times with deionized water to remove free cationic polyacrylamide, and the filtered and washed product was dried in a vacuum oven for 24 h to obtain cationic polyacrylamide-modified boron nitride.
[0034] As a preferred technical solution of the present invention, the epoxy resin includes liquid epoxy resin.
[0035] It should be noted that the liquid epoxy resin in the present invention refers to an epoxy resin that is liquid at room temperature (20-30° C.).
[0036] Preferably, the liquid epoxy resin includes any one of liquid bisphenol epoxy resin, liquid aminophenol epoxy resin, silicone-modified epoxy resin or naphthalene epoxy resin, or a combination of at least two thereof, and is further preferably any one of liquid bisphenol A epoxy resin, liquid bisphenol F epoxy resin, p-aminophenol liquid epoxy resin, 1,3-bis(3-glycidoxypropyl)tetramethyldisiloxane resin or a combination of at least two thereof.
[0037] Preferably, the epoxy equivalent of the epoxy resin is 100-300 g / eq, for example, it can be 100 g / eq, 120 g / eq, 140 g / eq, 160 g / eq, 180 g / eq, 200 g / eq, 220 g / eq, 240 g / eq, 260 g / eq, 280 g / eq or 300 g / eq, etc.
[0038] As a preferred technical solution of the present invention, the curing agent includes an aromatic amine curing agent.
[0039] Preferably, the aromatic amine curing agent is selected from any one or a combination of at least two of diaminodiphenylmethane (MDA), 4,4'-methylenedianiline, m-phenylenediamine (MPDA), diaminodiphenyl sulfone (DDS), diethyltoluenediamine (DETDA), diaminodiphenylmethane (DDM), 3,3'-diethyl-4,4'-diaminodiphenylmethane, 4,4'-methylenebis(N-methylaniline), trimethylenebis(4-aminobenzoate), polytetrahydrofuran-bis-p-aminobenzoate, methylenebis(2-ethyl-6-methylaniline), 4,4'-methylenebis(2,6-dimethylaniline), and 4,4'-methylenebis(2,6-diethylaniline), and is further preferably diethyltoluenediamine and / or 3,3'-diethyl-4,4'-diaminodiphenylmethane.
[0040] As a preferred technical solution of the present invention, the filler includes spherical nano-silicon dioxide.
[0041] Preferably, the average particle size of the spherical nano-silica is 5-20 μm, for example, it can be 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm or 20 μm, etc.
[0042] In a second aspect, the present invention provides a method for preparing the bottom filling glue as described in the first aspect, the preparation method comprising the following steps:
[0043] The components in the bottom filling glue and the solvent are mixed and dried to obtain the bottom filling glue.
[0044] As a preferred technical solution of the present invention, the preparation method comprises the following steps:
[0045] (1) mixing an epoxy resin, a filler, flake boron nitride and a solvent to obtain a mixture 1;
[0046] (2) mixing the mixture 1 obtained in step (1) with silver nanowires, and removing the solvent to obtain a mixture 2;
[0047] (3) Mixing the mixture 2 obtained in step (2) with a curing agent and drying the mixture to obtain the bottom filling adhesive.
[0048] As a preferred technical solution of the present invention, the solvent includes any one of tetrahydrofuran, anhydrous methanol or acetone, or a combination of at least two of them.
[0049] Preferably, the mass ratio of the epoxy resin to the solvent is ≥1:10 (for example, it may be 1:10, 1:20, 1:50, 1:80, 1:100, 1:120, 1:140, 1:160, 1:180, 1:200, 1:220, 1:240 or 1:250, etc.), and more preferably 1:(100-200).
[0050] Preferably, the mixing method in step (1) includes stirring, and the stirring speed is 450-550rpm (for example, it can be 450rpm, 460rpm, 470rpm, 480rpm, 490rpm, 500rpm, 510rpm, 520rpm, 530rpm, 540rpm or 550rpm, etc.), and the time is 3-8min (for example, it can be 3min, 4min, 5min, 6min, 7min or 8min, etc.).
[0051] Preferably, the mixing method in step (2) includes stirring, and the stirring speed is 450-550rpm (for example, it can be 450rpm, 460rpm, 470rpm, 480rpm, 490rpm, 500rpm, 510rpm, 520rpm, 530rpm, 540rpm or 550rpm, etc.), and the time is 3-8min (for example, it can be 3min, 4min, 5min, 6min, 7min or 8min, etc.).
[0052] Preferably, the method for removing the solvent in step (2) comprises rotary evaporation.
[0053] Preferably, the temperature for removing the solvent in step (2) is 45-55°C (for example, 45°C, 46°C, 47°C, 48°C, 49°C, 50°C, 51°C, 52°C, 53°C, 54°C or 55°C, etc.), and the time is 6-8h (for example, 6h, 6.5h, 7h, 7.5h or 8h, etc.).
[0054] Preferably, the mixing method in step (3) includes stirring, and the stirring speed is 450-550rpm (for example, it can be 450rpm, 460rpm, 470rpm, 480rpm, 490rpm, 500rpm, 510rpm, 520rpm, 530rpm, 540rpm or 550rpm, etc.), and the time is 3-8min (for example, it can be 3min, 4min, 5min, 6min, 7min or 8min, etc.).
[0055] Preferably, the drying method in step (3) comprises vacuum drying, the vacuum drying temperature is 35-45°C (for example, it can be 35°C, 36°C, 37°C, 38°C, 39°C, 40°C, 41°C, 42°C, 43°C, 44°C or 45°C, etc.), and the time is 50-70min (for example, it can be 50min, 52min, 54min, 56min, 58min, 60min, 62min, 64min, 66min, 68min or 70min, etc.).
[0056] As a preferred technical solution of the present invention, the preparation method of the bottom filling glue specifically comprises the following steps:
[0057] (1) stirring and mixing epoxy resin, filler, flake boron nitride and solvent at 450-550 rpm for 3-8 minutes to obtain a mixture 1;
[0058] (2) stirring the mixture 1 obtained in step (1) and the silver nanowires at 450-550 rpm, and then removing the solvent by rotary evaporation at 45-55° C. for 4-8 hours to obtain a mixture 2;
[0059] (3) Mixing the mixture 2 obtained in step (2) with the curing agent is stirred at 450-550 rpm for 3-8 min, and vacuum dried at 35-45° C. for 50-70 min to obtain the bottom filling glue.
[0060] In a third aspect, the present invention provides a use of the bottom filling adhesive as described in the first aspect, wherein the bottom filling adhesive is used for chip packaging.
[0061] Compared with the prior art, the present invention has the following beneficial effects:
[0062] (1) The present invention designs the specific composition of the bottom filling glue, further uses the synergistic effect of fillers, silver nanowires and flake boron nitride, and controls the dosage of silver nanowires and flake boron nitride within specific ranges, thereby preparing a bottom filling glue with high thermal conductivity and high fluidity as well as good mechanical properties.
[0063] (2) The present invention further improves the comprehensive performance of the bottom filling glue through the synergistic effect of silver nanowires with high aspect ratio and modified boron nitride flakes of specific size and fillers. BRIEF DESCRIPTION OF THE DRAWINGS
[0064] Figure 1 is a SEM image of the silver nanowires used in Example 1 of the present invention, with a scale of 2 μm;
[0065] Figure 2 is a SEM image of the modified flake boron nitride used in Example 1 of the present invention, with a scale of 10 μm;
[0066] Figure 3 This is a SEM image of the bottom filling glue provided in Example 1 of the present invention, with a scale of 20 μm;
[0067] Figure 4 This is a SEM image of the bottom filling glue provided in Example 10 of the present invention, with a scale of 5 μm;
[0068] Figure 5 This is a SEM image of the bottom filling glue provided in Comparative Example 5 of the present invention, with a scale of 40 μm;
[0069] Figure 6 Schematic diagram of the effect of modified BN and epoxy resin (EP) in the bottom filling glue provided in Example 1 of the present invention;
[0070] Figure 7 A schematic diagram of the structure of modified BN, silver nanowires and spherical silica fillers in the bottom filling glue provided in Example 1 of the present invention;
[0071] Figure 8Schematic diagram of heat conduction of the bottom filling glue provided in Example 1 of the present invention. DETAILED DESCRIPTION
[0072] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0073] The sources of some components in the following examples and comparative examples are as described in Table 1:
[0074] Table 1
[0075]
[0076] The above silver nanowires with different aspect ratios were prepared with reference to “Synthesis of Silver Nanowires and Their Application in Configurational Electronic Devices, Yu Xuecheng, Shenzhen Institutes of Advanced Technology, Chinese Academy of Sciences”.
[0077] Preparation Example 1, Comparative Preparation Example 1
[0078] Preparation Example 1 and Comparative Preparation Example 1 respectively provide a cationic polyacrylamide-modified boron nitride (CPAM-modified BN, abbreviated as CBN) and a preparation method thereof. The specific preparation methods are as follows:
[0079] BN powder and deionized water in a mass ratio of 1:10 were placed in a flask equipped with a mechanical stirrer, and then ultrasonically treated for 10 min at a power of 200 W, and then mechanically stirred at 500 rpm for 5 min to obtain a BN suspension;
[0080] Then, a 1 wt% cationic polyacrylamide aqueous solution (cationic polyacrylamide was purchased from Aladdin, item number P754420) was added dropwise to the BN suspension until the suspension became transparent to obtain a mixture, and the obtained mixture was filtered and washed three times with deionized water to remove free cationic polyacrylamide, and the filtered and washed product was dried in a vacuum oven for 24 h to obtain cationic polyacrylamide-modified boron nitride (CPAM-modified BN, abbreviated as CBN).
[0081] Example 1-Example 12, Comparative Example 1-Comparative Example 7
[0082] Example 1 to Example 12 and Comparative Example 1 to Comparative Example 7 respectively provide a bottom filling glue, and the specific composition of the bottom filling glue is shown in Table 2 to Table 4 below. The amount of each component in Table 2 to Table 4 is in parts by weight.
[0083] The preparation method of the above bottom filling glue is as follows:
[0084] (1) stirring and mixing epoxy resin, filler, flake boron nitride and tetrahydrofuran at 500 rpm for 5 minutes to obtain a mixture 1;
[0085] (2) stirring the mixture 1 obtained in step (1) and the silver nanowires (the silver nanowires were added three times) at 500 rpm for 10 min, and then removing the solvent by rotary evaporation at 50° C. to obtain a mixture 2;
[0086] (3) The mixture 2 obtained in step (2) was stirred and mixed with the curing agent at 500 rpm for 5 min, and vacuum dried at 40° C. for 60 min to obtain the bottom filling glue.
[0087] The performance of the bottom filling glue provided in the above embodiment and comparative example was tested, and the specific testing method is as follows:
[0088] Thermal conductivity test (K pcb / (W / mx℃)): The bottom filling glue provided in the above embodiments and comparative examples was injected into the mold to prepare a sample with a length of 25mm×width of 25mm×thickness of 2mm, and its thermal conductivity was tested using an interface material thermal resistance and thermal conductivity coefficient tester (Ruiling LW-9389);
[0089] Fracture toughness (K 1c / (MPa·m 1 / 2 )) Determination: The bottom filling glue provided in the above embodiments and comparative examples was injected into a mold to prepare a sample of 35 mm in length × 7 mm in width × 3 mm in thickness. The mechanical properties of the sample were measured using an electronic universal testing machine (Shimadzu AGX-10kNVD). When making the sample, a crack was introduced in the middle with a blade;
[0090] Viscosity: measured using a rotational rheometer (Netzsch Kinexus Prime DSR-III).
[0091] The above performance test results are shown in Table 2-Table 4 below:
[0092] Table 2
[0093]
[0094]
[0095] Table 3
[0096]
[0097] Table 4
[0098]
[0099] The microscopic morphology of the bottom filling glue provided in Example 1, Example 10, Comparative Example 5 and Comparative Example 7 was characterized using a scanning electron microscope, and the SEM images thereof are shown in order. Figure 3-Figure 5 shown.
[0100] Figure 3 This shows that silicon dioxide and boron nitride are evenly dispersed in epoxy resin. Figure 4 It can be seen that boron nitride has a more consistent orientation in the resin, which helps to conduct heat. Figure 5 Silver nanowires can be seen in the
[0101] The modified boron nitride used in Example 1 of the present invention is obtained by modifying boron nitride with cationic polyacrylamide. The modification schematic diagram is shown in FIG. Figure 6 shown.
[0102] Figure 7 This is a schematic diagram of the structure of modified BN, silver nanowires and spherical silica fillers in the bottom filling glue provided in Example 1 of the present invention.
[0103] The schematic diagram of heat conduction of the bottom filling glue provided in Example 1 of the present invention is as follows Figure 8 As shown, the thermal conductive network composed of BN and silver nanowires can improve the heat transfer flux
[0104] From the above content, it can be seen that the present invention designs the specific composition of the bottom filling glue, further through the synergistic effect of filler, silver nanowires and flake boron nitride, and controls the amount of silver nanowires and flake boron nitride in a specific range, to prepare a bottom filling glue with high thermal conductivity and high fluidity and good mechanical properties. The thermal conductivity (K pcb ) is 0.769-1.253W / mx℃, fracture toughness (K 1c ) is 2.458-2.944MPa·m 1 / 2 , viscosity is 38.456-41.546Pa·s.
[0105] As can be seen from Examples 1-7, the present invention further improves the comprehensive performance of the bottom filler by the synergistic effect of the silver nanowires with high aspect ratio and the modified boron nitride flakes with specific size and the filler, and its thermal conductivity (K pcb ) is 1.038-1.253W / mx℃, fracture toughness (K 1c ) is 2.563-2.944MPa·m 1 / 2 , viscosity is 38.456-41.346Pa·s.
[0106] It can be seen from Example 1, Examples 8-12, and Comparative Examples 1-4 that the present invention prepares an underfill adhesive with excellent performance by controlling the amount of silver nanowires and flaky boron nitride within a specific range.
[0107] It can be seen from Example 1 and Comparative Examples 5-7 that the present invention prepares a bottom filling glue with excellent performance through the synergistic effect of filler, silver nanowires and flake boron nitride.
[0108] In summary, the present invention designs the specific composition of the bottom filling glue, further through the synergistic effect of fillers, silver nanowires and flake boron nitride, and controls the dosage of silver nanowires and flake boron nitride within specific ranges, thereby preparing a bottom filling glue with high thermal conductivity and high fluidity as well as good mechanical properties, which can be used for chip packaging.
[0109] The applicant declares that the present invention illustrates the detailed process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A bottom filling glue, characterized in that: The bottom filling glue comprises the following components in parts by weight:
2. The bottom filling glue according to claim 1, characterized in that: The aspect ratio of the silver nanowire is ≥150; Preferably, the silver nanowire has a length of 10-20 μm and a diameter of 20-60 nm.
3. The bottom filling glue according to claim 1 or 2, characterized in that: The average particle size of the flake boron nitride is 3-5 μm; Preferably, the thickness of the flake boron nitride is less than 100 nm; Preferably, the flaky boron nitride comprises modified flaky boron nitride, and the modifier of the modified flaky boron nitride comprises any one or a combination of at least two of cationic polyacrylamide, anionic polyacrylamide, zwitterionic polyacrylamide and nonionic polyacrylamide, and is further preferably cationic polyacrylamide; Preferably, the mass ratio of the modifier to the flaky boron nitride is 1:(100-200).
4. The bottom filling glue according to any one of claims 1 to 3, characterized in that: The epoxy resin includes liquid epoxy resin; Preferably, the liquid epoxy resin includes any one of liquid bisphenol epoxy resin, liquid aminophenol epoxy resin, silicone-modified epoxy resin or naphthalene epoxy resin, or a combination of at least two thereof, and more preferably any one of liquid bisphenol A epoxy resin, liquid bisphenol F epoxy resin, p-aminophenol liquid epoxy resin, 1,3-bis(3-glycidoxypropyl)tetramethyldisiloxane resin or naphthalene epoxy resin, or a combination of at least two thereof; Preferably, the epoxy equivalent of the epoxy resin is 100-300 g / eq.
5. The bottom filling glue according to any one of claims 1 to 4, characterized in that: The curing agent includes an aromatic amine curing agent; Preferably, the aromatic amine curing agent is selected from any one or a combination of at least two of diaminodiphenylmethane, 4,4'-methylenedianiline, m-phenylenediamine, diaminodiphenyl sulfone, diethyltoluenediamine, diaminodiphenylmethane, 3,3'-diethyl-4,4'-diaminodiphenylmethane, 4,4'-methylenebis(N-methylaniline), trimethylenebis(4-aminobenzoate), polytetrahydrofuran-bis-p-aminobenzoate, methylenebis(2-ethyl-6-methylaniline), 4,4'-methylenebis(2,6-dimethylaniline), and 4,4'-methylenebis(2,6-diethylaniline), and is further preferably diethyltoluenediamine and / or 3,3'-diethyl-4,4'-diaminodiphenylmethane.
6. The bottom filling glue according to any one of claims 1 to 5, characterized in that: The filler includes spherical nano-silicon dioxide; Preferably, the average particle size of the spherical nano-silicon dioxide is 5-20 μm.
7. A method for preparing the bottom filling glue according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: The components in the bottom filling glue and the solvent are mixed and dried to obtain the bottom filling glue.
8. The preparation method according to claim 7, characterized in that: The preparation method comprises the following steps: (1) mixing an epoxy resin, a filler, flake boron nitride and a solvent to obtain a mixture 1; (2) mixing the mixture 1 obtained in step (1) with silver nanowires, and removing the solvent to obtain a mixture 2; (3) Mixing the mixture 2 obtained in step (2) with a curing agent and drying the mixture to obtain the bottom filling adhesive.
9. The preparation method according to claim 8, characterized in that: The solvent includes any one of tetrahydrofuran, anhydrous methanol or acetone or a combination of at least two thereof; Preferably, the mass ratio of the epoxy resin to the solvent is ≥1:10; Preferably, the mixing method in step (1) comprises stirring, and the stirring speed is 450-550 rpm and the time is 3-8 min; Preferably, the mixing method in step (2) comprises stirring, and the stirring speed is 450-550 rpm and the time is 3-8 min; Preferably, the method for removing the solvent in step (2) comprises rotary evaporation; Preferably, the temperature for removing the solvent in step (2) is 45-55°C and the time is 6-8h; Preferably, the mixing method in step (3) comprises stirring, and the stirring speed is 450-550 rpm and the time is 3-8 min; Preferably, the drying method in step (3) comprises vacuum drying, and the vacuum drying temperature is 35-45° C. and the time is 50-70 min.
10. An application of the bottom filling adhesive according to any one of claims 1 to 6, characterized in that: The bottom filling glue is used for chip packaging.
Citation Information
Patent Citations
Insulating heat-conductive adhesive and preparation method thereof
CN105754535A
High-polymer epoxy heat-conducting material and preparation method thereof
CN106751477A
Nylon composite material and preparation method thereof
CN116554628A